Construção e implementação de UEPS: contribuições para aprendizagem significativa de conceitos de eletrodinâmica - Clave, Gilliane Hoehr (2019)
This paper presents a research about the construction and implementation of Potentially Meaningful Teaching Units (PMTU) and their contributions for meaningful learning of electrodynamics concepts. The research is based on the Meaningful Learning of David Ausubel and Critical Meaningful Learning of Marco Antonio Moreira. In this sense, it is seeked to understand in which way the PMTU conttribute at meaningful learning these concepts on students of a third year of a Santa Maria´s/RS public high school. To the development of this paper, it were elaborated three PMTU, in which it has been tried to cotemplate diversified activities and related to the students routine. In the first PMTU, the concepts of voltage and electric current, electrical resistance and the Ohm´s law were approached. On the second, it has been approached the concepts of electric power and eletric energy, and so its own transformations. In the third PMTU, the concepts related with the operation of eletric circuits were presented. These three Teaching Units were implemented from Setember to November of 2018 in two classes of the third year. The main objective of this research was to identify how the aplication of PMTU can help in the Meaningful Teaching of presented subject concepts. To reach the objective, we used the following gathering data instruments: interview to identify the student`s previous knowledge, a quiz to seek some indications of Meaningful Teaching and concept maps built by the students in their first PMTU and by the end of the implemented activities. To do that we used the contente analysis, according to Bardin (2011), which is characterized as a set of communication analysis techniques. By doing this analysys, we reached indications of Meaningful Teaching of the main concepts envolved.